Economic Evaluation of First-Line Atezolizumab for Extensive-Stage Small-Cell Lung Cancer in the US - Wang, Yingcheng; Rui, Mingjun; Yang, Lan; Wang, Xintian; Shang, Ye; Ma, Aixia; Li, Hongchao (Frontiers in Public Health, 2021)
Abstract Introduction: This study evaluated the cost-effectiveness of atezolizumab + chemotherapy versus chemotherapy as first-line treatment for extensive-stage small-cell lung cancer (SCLC) in the United States (US). Methods: The 3 health states partitioned survival (PS) model was used over the lifetime. Effectiveness and safety data were derived from the IMpower133 trial. The parametric survival model and mixture cure model were used for the atezolizumab + chemotherapy group to explore the long-term uncertainty of the effect of immunotherapy, and the parametric survival model was used for the chemotherapy group. Costs were derived from the pricing files of Medicare and Medicaid Services, and utility values were derived from previous studies. Sensitivity analyses were performed to observe model stability. Results: If the mixture cure model was considered for the intervention group, compared with chemotherapy alone, atezolizumab + chemotherapy yielded an additional 0.11 quality-adjusted life-years (QALYs), with an incremental cost of US84,257. The incremental cost-utility ratio (ICUR) was US785,848/QALY. If the parametric survival model was considered for the intervention group, atezolizumab + chemotherapy yielded an additional 0.10 QALYs, with an incremental cost of US84,257; the ICUR was US827,610/QALY. In the one-way sensitivity analysis, progression-free (PF) and postprogression (PP) utilities were the main drivers. In the scenario analysis (PF utility=0.673, PP utility =0.473), the results showed that the ICUR was US910,557/QALY and US965,607/QALY when the mixture cure model and parametric survival model was considered for the intervention group, respectively. In the PSA, the probabilities that atezolizumab + chemotherapy would not be cost-effective were 100% if the willingness-to-pay threshold was US100,000/QALY. Conclusions: The findings of the present analysis suggest that atezolizumab + chemotherapy is not cost-effective in patients receiving first-line treatment for extensive-stage SCLC in the US.